2007
DOI: 10.1002/ange.200700008
|View full text |Cite
|
Sign up to set email alerts
|

Rationales Design von hoch aktiven und selektiven Liganden für α5β1‐ und αvβ3‐Integrine

Abstract: Integrine sind heterodimere Zelladhäsionsrezeptoren, die an einer Vielzahl pathologischer Prozesse wie der Metastasierung von Tumoren, Thrombose, Entzündungen und Osteoporose beteiligt sind.[3] Sie sind daher seit geraumer Zeit wichtige Ziele in der pharmazeutischen Industrie.[4] Seit Brooks et al. berichteten, dass das von uns entwickelte[5a] das die Integrine avb3 und avb5 bindet, durch Angiogenese-Inhibierung das Tumorwachstum hemmt, [6] wurden viele avb3-Liganden entwickelt, von denen einige bereits klinis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
1
17
0
7
Order By: Relevance
“…To understand the selectivity profile of the most interesting peptides, we determined the three-dimensional structures of peptides 11 and 13 by solution-state NMR spectroscopy and molecular dynamics (MD) calculations [22,23] (Figure 1) and docked each to both the avb3 receptor (X-ray structure of the Cilengitide-avb3 complex [24] ) and the a5b1 receptor (homology model [25] ; see the Supporting Information). (A detailed description of the structure calculations is given in the Supporting Information.…”
mentioning
confidence: 99%
“…To understand the selectivity profile of the most interesting peptides, we determined the three-dimensional structures of peptides 11 and 13 by solution-state NMR spectroscopy and molecular dynamics (MD) calculations [22,23] (Figure 1) and docked each to both the avb3 receptor (X-ray structure of the Cilengitide-avb3 complex [24] ) and the a5b1 receptor (homology model [25] ; see the Supporting Information). (A detailed description of the structure calculations is given in the Supporting Information.…”
mentioning
confidence: 99%
“…These findings motivated us to systematically elucidate the potential of hydroxamic acids as integrin ligands as well as the structural and electronic aspects of the observed selectivity. In our previous studies we found that the spatial orientation of the aromatic moiety in the vicinity of the carboxylic acid determines the selectivity of the ligand; a mesitylene carboxamide unit led to α5β1 selectivity, while a sulfonamide group yielded biselective ligands 14bd. We were expecting that the replacement of the carboxylate by a hydroxamate should have a high impact on the positioning of this group, so six pairs of ligands, all containing a 2‐aminoyridine group as the basic moiety, were synthesized and evaluated for their activity and selectivity profile.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we prepared the hydroxamate analogue of an αvβ3 selective ligand based on an elongated β‐homotyrosine. We also preapared another compound library based on a lead structure comprising a tetrahydropyrimidine as the basic moiety and a benzosulfonamide substituent, which was previously found to give ligands with high affinity for αvβ3 and moderate affinity for α5β1 14b,c. Variations of the carboxylic acid function including an ester, amide, acylhydrazine, and N ‐methyl hydroxamic acid should reveal, whether other carboxylic acid derivatives lead to changes in affinity and selectivity comparable to hydroxamic acids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kürzlich haben wir RGD-basierte Integrinantagonisten entwickelt, die spezifisch entweder a5b1 oder avb3 adressieren, während keine Aktivität gegenüber dem Blutplättchenintegrin aIIbb3 vorliegt. [11] Diese Peptidmimetika (1 und 2) wurden mit 1-((1,3-Dicarboxy)propyl)-4,7-(carboxymethyl)-1,4,7-triazacyclononan (NODAGA), einem weitverbreiteten difunktionellen Chelator, [12] funktionalisiert, wodurch die a5b1-selektive Verbindung 3 und die avb3-selektive Verbindung 4 erhalten wurden (Tabelle 1). Die Bestimmung der IC 50 -Werte in einem kürzlich beschriebenen, kompetitiven Integrinbindungsassay [13] Die a5b1-selektive Verbindung 3 adressierte spezifisch den a5b1-exprimierenden Tumor in der rechten Schulter der Maus (Abbildung 1 A).…”
Section: Angewandte Zuschriftenunclassified